2017
DOI: 10.18291/njwls.v7i4.102359
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Conceptions of Coworkership in a Swedish Health Care Organization

Abstract: The concept of coworkership is widely established as a top-down communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…Only a few studies about co-workership have been published in peer-reviewed journals and none of them in the context of pharmacies. Bergman et al (2017) conducted a study on how employees in healthcare perceived co-workership and concluded that trusting each other's competencies, common goals, and working over professional or organizational boundaries was important. In that study, co-workership was viewed as a collective process formed around the patient.…”
Section: Theoretical Framework and Earlier Researchmentioning
confidence: 99%
“…Only a few studies about co-workership have been published in peer-reviewed journals and none of them in the context of pharmacies. Bergman et al (2017) conducted a study on how employees in healthcare perceived co-workership and concluded that trusting each other's competencies, common goals, and working over professional or organizational boundaries was important. In that study, co-workership was viewed as a collective process formed around the patient.…”
Section: Theoretical Framework and Earlier Researchmentioning
confidence: 99%
“…From this point of view, all actors should mobilize to promote a shared representation of this boundary object while adapting it to their own needs and preferences. (Bergman et al, 2017). This can challenge their commitment to the development of the program and the boundaries of their participation.…”
Section: The Co-production Of a Boundary Object: Whp Programs As Spac...mentioning
confidence: 99%
“…Mūsų tyrimo duomenimis, išanalizavus slaugytojų darbo patirties vertinimą, geriausiai slaugytojai vertino savo darbo prasmingumą, bendradarbių pagalbą ir palaikymą. C. Bergman et al (2017) teigia, kad glaudus bendradarbiavimas darbe siejasi su bendru komandos klimatu, o tai turi įtakos ne tik pacientų priežiūros kokybės rezultatams, bet ir sveikatą stiprinančios darbo aplinkos palaikymui. Taigi, tiek analogiškų tyrimų R. Burke, L. Fiksenbaum (2009), tiek mūsų tyrimo rezultatai rodo, kad sveikatos priežiūros specialistai, kurie palankiau vertina savo sveikatą, pozityviau vertina ir darbo patirtį.…”
Section: Rezultatų Aptarimasunclassified
“…Darbo aplinkos veiksnių įtaka slaugytojų sveikatai nys turintis tiek teigiamą, tiek neigiamą poveikį dirbančiųjų gyvenimo kokybei ir sveikatai. C. Bergman et al (2017) nurodo, kad darbo pobūdis sveikatos priežiūros organizacijose apima glaudžius ryšius su pacientais ir atsakomybę už jų sveikatą bei gerovę. Nuolat vykstant sveikatos reformoms, didėja reikalavimai sveikatos priežiūros specialistams.…”
unclassified